2020
DOI: 10.3390/robotics9030062
|View full text |Cite
|
Sign up to set email alerts
|

Forward Kinematic Model Resolution of a Special Spherical Parallel Manipulator: Comparison and Real-Time Validation

Abstract: This paper deals with a special architecture of Spherical Parallel Manipulators (SPMs) designed to be a haptic device for a medical tele-operation system. This architecture is obtained by replacing the kinematic of one leg of a classical 3-RRR SPM (R for revolute joint). The Forward Kinematic Model (FKM) is particularly addressed to allow the new master device to control the motion of a slave surgical robot. For this purpose, three methods are presented to solve the FKM and compared based on the criterion of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…So far, most studies have focused on the kinematic issues of RSPMs, while quite a few have referred to the dynamic control of these robots. For RSPMs, several studies have been reported on a variety of relevant problems, which include modeling of workspace in joint and Cartesian space [14][15][16][17], inverse and forward kinematic analysis to obtain analytically unique real-time solutions [18][19][20][21][22][23][24][25], design and optimization [26][27][28][29][30][31][32], design and robustness [33], singularity analysis, and derivation of Jacobian matrices [34,35]. However, the constrained kinematic analysis has gone unnoticed in the literature.…”
Section: Mathematical Modeling Challenges and Control Strategiesmentioning
confidence: 99%
“…So far, most studies have focused on the kinematic issues of RSPMs, while quite a few have referred to the dynamic control of these robots. For RSPMs, several studies have been reported on a variety of relevant problems, which include modeling of workspace in joint and Cartesian space [14][15][16][17], inverse and forward kinematic analysis to obtain analytically unique real-time solutions [18][19][20][21][22][23][24][25], design and optimization [26][27][28][29][30][31][32], design and robustness [33], singularity analysis, and derivation of Jacobian matrices [34,35]. However, the constrained kinematic analysis has gone unnoticed in the literature.…”
Section: Mathematical Modeling Challenges and Control Strategiesmentioning
confidence: 99%
“…1, which consists of two parts: the 3RRR parallel mechanism and the 3D moving mechanism. 3RRR parallel mechanism is used for the 3D rotational reduction [20]- [22], and the 3D moving mechanism is used for 3D moving reduction. 3RRR parallel mechanism is fixedly connected to the injured pelvis by a pelvic clamping instrument.…”
Section: Robot Architecturementioning
confidence: 99%
“…In [14,16], a manipulator for precise and high-speed orientation of a camera-the Agile Eye-was built. In [17][18][19] the manipulator was utilized as an device for surgery applications and in [20] in a human hip exoskeleton context. In combination with the knee joint, each leg of the robot is a serial-parallel-manipulator on its own, which is connected by the central torso part.…”
Section: Internal Mechanical Designmentioning
confidence: 99%
“…As it can be observed in Equations ( 18) and (19), it is possible to decompose the matrices X * and Y * into X * = X D and Y * = Y D with the diagonal matrix…”
Section: Mathematical Derivationmentioning
confidence: 99%
See 1 more Smart Citation